Adolescent substance use and educational attainment: An integrative data analysis comparing cannabis and alcohol from three Australasian cohorts. (1st November 2015) - Silins, Edmund; Fergusson, David M.; Patton, George C.; Horwood, L. John; Olsson, Craig A.; Hutchinson, Delyse M.; Degenhardt, Louisa; Tait, Robert J.; Borschmann, Rohan; Coffey, Carolyn; Toumbourou, John W.; Najman, Jake M.; et al.
Highlights: Adolescent cannabis use increased the odds of non-progression with formal education. Associations for adolescent alcohol use were inconsistent and weaker. Cannabis use accounted for a greater proportion of the overall rate of educational underachievement than alcohol use. Findings inform the debate about the relative harms of cannabis and alcohol use. Abstract: Background: The relative contributions of cannabis and alcohol use to educational outcomes are unclear. We examined the extent to which adolescent cannabis or alcohol use predicts educational attainment in emerging adulthood. Methods: Participant-level data were integrated from three longitudinal studies from Australia and New Zealand (Australian Temperament Project, Christchurch Health and Development Study, and Victorian Adolescent Health Cohort Study). The number of participants varied by analysis ( N  = 2179–3678) and were assessed on multiple occasions between ages 13 and 25. We described the association between frequency of cannabis or alcohol use prior to age 17 and high school non-completion, university non-enrolment, and degree non-attainment by age 25. Two other measures of alcohol use in adolescence were also examined. Results: After covariate adjustment using a propensity score approach, adolescent cannabis use (weekly+) was associated with 1½ to two-fold increases in the odds of high school non-completion (OR = 1.60, 95% CI = 1.09–2.35), university non-enrolment (OR = 1.51, 95% CI = 1.06–2.13), and degree non-attainment (OR = 1.96, 95% CI = 1.36–2.81). In contrast, adjusted associations for all measures of adolescent alcohol use were inconsistent and weaker. Attributable risk estimates indicated adolescent cannabis use accounted for a greater proportion of the overall rate of non-progression with formal education than adolescent alcohol use. Conclusions: Findings are important to the debate about the relative harms of cannabis and alcohol use. Adolescent cannabis use is a better marker of lower educational attainment than adolescent alcohol use and identifies an important target population for preventive intervention.